PtTe Monolayer: Two-Dimensional Electrocatalyst with High Basal Plane Activity toward Oxygen Reduction Reaction - Wang, Yu; Li, Yafei; Heine, Thomas (Journal of the American Chemical Society, 2018)
PtTe is a layered bulk material that was discovered in 1897. According to first-principles calculations, it is one of the few layered materials that maintains structure and metallic character when thinned down to the monolayer. Interlayer energy is small enough to allow for chemical exfoliation techniques. Our calculations show that monolayer PtTe is a candidate to substitute Pt electrodes, and we computationally studied its catalytic performance in the oxygen reduction reaction (ORR). Remarkably, the basal plane of a PtTe monolayer exhibits excellent catalytic activity toward ORR, with a positive half-wave potential (∼0.90 V) and a high four-electron reduction pathway selectivity. These characteristics suggest that it outperforms Pt electrodes as catalyst, has a reduced Pt content, high Pt utilization, and a high surface area, and is a promising candidate for fuel cell components.
CRIS-Team Scopus Importer:2022-04-14